Just Transition and Catholic Social Thought in the Philippine Context - Puen, Stephanie Ann Y. (Archīum Ateneo, 2024)
Just transition is a concept used to describe how communities should navigate the shift toward a more sustainable way of living. This paper discusses the contribution of Catholic Social Thought to understanding just transition and how it can be applied to a particular context—in this case, the Philippine setting. Specifically, this paper will discuss the concepts of justice, the common good, and subsidiarity, and how these can elaborate on what a just transition is.